Analysis of the Determinants of Third Party Funds PT. Bank Muamalat Indonesia Tbk - devi yana; Windari windari; ali hardana; abdul nasser hasibuan (Institut Agama Islam Negeri Padangsidimpuan, 2020)
Third Party Funds (DPK) consist of demand deposits, savings, time deposits. The increase in DPK at PT. bank Muamalat Indonesia Tbk, continued to increase from 2010-2014 but decreased from 2015-2016 and increased again in 2017 then decreased again in 2018. The increase and decrease in the amount of DPK PT. Bank Mualamat Indonesia is of course influenced by several factors including inflation, BI Rate, exchange rate, and the money supply. This research is a quantitative research. the data used is time series data for the quarter 2010-2018 published by Bank Indonesia and PT. Bank Muamalat Indonesia Tbk. through the official website www. bi.go id and www.bankmuamalat.co.id were analyzed using eviews9. The results of this study indicate that inflation partially affects TPF. The BI Rate has a partial effect on DPK. The Rupiah Exchange Rate partially has a negative effect on DPK. The amount of the Money Supply has a partial effect on DPK. And Inflation, BI Rate, Rupiah Exchange Rate and Money Supply have a simultaneous effect on DPK.